PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA KOPILOKA 3.0 PALEMBANG TAHUN 2021 - Juni Eliana Prasetya N; Moh. Faizal; Choirunnisak Choirunnisak (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
In this study, there are results that contradict the theory which states that the higher the level of training and motivation, the employee's performance should increase. In this study, training had no effect and motivation had no positive effect. This study aims to determine the effect of training and work motivation on employee performance in Kopiloka 3.0. The population in this study were all employees at Kopiloka 3.0, which amounted to 15 people with a sample of 15 people using saturated sampling. The data analysis technique in this study used SPSS 24 software, which consisted of data quality test, classical assumption test, multiple regression analysis, and hypothesis testing. By using multiple regression analysis, the results of the study show that training has no effect on employee performance. Motivation has a significant effect on employee performance. Simultaneously (together) the independent variables of training and motivation have an effect on employee performance.